2016
DOI: 10.1111/jvim.13924
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Spec fPLand 1,2‐o‐Dilauryl‐Rac‐Glycero‐3‐Glutaric Acid‐(6′‐Methylresorufin) Ester Assay in 60 Cats Using Standardized Assessment of Pancreatic Histology

Abstract: BackgroundFeline pancreas‐specific lipase (Spec fPL) is considered a useful test for the antemortem diagnosis of pancreatitis in cats. A recent study found good agreement between the results of the Spec fPL and catalytic 1,2‐o‐dilauryl‐rac‐glycero‐3‐glutaric acid‐(6′‐methylresorufin) ester (DGGR) lipase assay. Prospective studies evaluating their sensitivity and specificity are lacking.ObjectivesTo compare the results of the Spec fPL and the DGGR assays with a standardized histologic assessment of the pancreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 20 publications
3
68
0
Order By: Relevance
“…Overall specificity was 91% (100% in healthy cats and 67% in symptomatic cats with normal pancreatic histology) (Forman et al, 2004). Another study evaluated the Spec fPL and also found 100% sensitivity for severe chronic pancreatitis; specificity, however, was only 54% (Oppliger et al, 2013a). These numbers nicely demonstrate the problems associated with the measurement of the fPLI/Spec fPL test: In cats with severe pancreatitis, the test will usually be positive, whereas it may be negative in mild disease.…”
Section: Pancreatic Enzymesmentioning
confidence: 81%
“…Overall specificity was 91% (100% in healthy cats and 67% in symptomatic cats with normal pancreatic histology) (Forman et al, 2004). Another study evaluated the Spec fPL and also found 100% sensitivity for severe chronic pancreatitis; specificity, however, was only 54% (Oppliger et al, 2013a). These numbers nicely demonstrate the problems associated with the measurement of the fPLI/Spec fPL test: In cats with severe pancreatitis, the test will usually be positive, whereas it may be negative in mild disease.…”
Section: Pancreatic Enzymesmentioning
confidence: 81%
“…Serum thyroxine concentration was measured in 18 cats, and four cats were diagnosed with hyperthyroidism. All cats were evaluated for pancreatitis by the DGGR‐lipase activity assay; 4 of 20 cats had minimally elevated values (28, 32, 32, and 34 U/L; reference range, 8–26 U/L) with unclear significance, and one cat had a value of 73 U/L, which was considered diagnostic for pancreatitis . Serum trypsinogen‐like immunoreactivity (fTLI) was measured in all 20 cats, and none had values that were diagnostic (<8 μg/L) or suspicious (8–12 μg/L) of exocrine pancreatic insufficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Soon after it was introduced as a method to measure pancreatic lipase activity in people, the DGGR‐based assay began to be used for serum lipase activity measurements in cats 12,15 and dogs 11,16,17,33 . Few studies have evaluated the clinical utility of DGGR‐based assays for the diagnosis of feline and canine pancreatitis 11,17,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Since 2005, various DGGR‐based assay validation studies for diagnosing pancreatitis in cats 12,15 and dogs 11,16,17 have been performed. These studies show good precision, linearity, and substantial agreement with Spec PL concentrations, with varying diagnostic sensitivities (cats: 36.8‐66.7% 12,15 ; dogs: 85.7‐93.0% 11,17 ) and specificities (cats: 63.0‐100.0% 12,15 ; dogs: 53.0‐74.3% 11,17 ). However, none of these validation studies investigated the effects of extrapancreatic lipases on DGGR‐based assays.…”
Section: Introductionmentioning
confidence: 99%